Increasing Network Efficiency. (Communications of the ACM, 2008)
The article reports that researchers have created an algorithm that may dramatically increase network routing efficiency. The algorithm is called XL, for approximate link state. Topics include boosting network routing efficiency by suppressing system updates, connected networks that are forced to continuously recalculate their Internet paths, and the reduction of overhead associated with route recomputation after a network change. Also discussed are networks that are comprised of low-power devices of slow links.